(untitled) (REVISTA NODO, 2019)
The coatings have the function of protecting the support wall from exogenous agents that may affect and degrade it. In the field of heritage, one of the most used mortars until the end of the 18th century in Colombia was the earth-based coating. This coating served as protection for walls built on the same land as the wall, the adobe or the bahareque with which it is considered to be built at least 90% of the historic centers of our country. For its development, the behavior of the different components such as soil, stabilizers, additives, binders and water must be taken into account. However, in Colombia there are few studies that determine the characteristics of these finishes in heritage buildings. That is why it is proposed in this article to inquire about the state of the art about the study of mortars on land, which allows us to approach and have the theoretical basis to carry out the characterization and behavior studies of these, so that they respond not only to the needs of restaurateurs, but to those who are interested in its application in current buildings.